Hubungan volume dan derajat keasaman (ph) saliva terhadap kejadian karies anak usia 7-9 tahun di Sekolah Dasar Negeri 5 Sumerta Denpasar - Putu Gde Adhi Paramanandana; Mia Ayustina Prasetya; Desak Nyoman Ari Susanti (Bali Dental Journal, 2020)
Background: The most common dental and oral diseases in Indonesia is caries. 7-9 years old is the age with highest dental and mouth problems in Indonesia. There are four main factors interacting in caries formation such as: host, substrate/diet, bacteria/microorganism and time. Saliva is one of the host factors that cause caries. There are several factors that influence the composition and salivary concentration such as volume and degree of acidity (pH) of saliva.The purpose of this experiment was to determine the relationship between volume and degree of acidity (pH) saliva with the occurrence of dental caries on children between 7-9 years old in Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali.Methods: The study design used was cross-sectional analytic. The samples were children between 7-9 years old in Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali. Sampling techniques using consecutive sampling technique of 65 children. Samples who have been allowed by their parents through informed consent, calculated the amount of their saliva volume and degree of acidity (pH), then examined the oral cavity to know the index of dental caries. The analytical test using chi-square methods.Result: The analytical test showed a value p = 0.041 for relation between volume saliva with the occurrence of dental caries and p = 0.028 for relation between salivary pH with the occurrence of dental caries.Conclusion: there is correlation between volume and degree of acidity (pH) of saliva with the occurrence of dental caries incidence on children between 7-9 years old in Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali. Latar Belakang: Penyakit gigi dan mulut yang paling sering terjadi di Indonesia adalah karies. Usia 7-9 tahun merupakan usia dengan tingkat masalah gigi dan mulut tertinggi di Indonesia. Terdapat empat faktor utama yang saling berinteraksi dalam pembentukan karies yaitu host, substrat/diet, bakteri/mikroorganisme dan waktu. Saliva merupakan salah satu host yang menjadi faktor penyebab karies. Terdapat beberapa faktor yang mempengaruhi komposisi dan konsentrasi saliva antara lain volume dan derajat keasaman (pH) saliva. Tujuan dari penelitian ini adalah untuk mengetahui hubungan volume dan derajat keasaman (pH) saliva terhadap kejadian karies anak usia 7-9 tahun di Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali.Metode: Desain penelitian menggunakan cross-sectional analitik. Sampel penelitian adalah anak Sekolah Dasar usia 7-9 tahun di Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali. Teknik pengambilan sampel menggunakan consecutive sampling dengan jumlah sampel sebanyak 65 anak. Anak yang telah diizinkan oleh orang tuanya melalui inform consent, dihitung jumlah volume dan pH salivanya, kemudian dilakukan pemeriksaan rongga mulut untuk mengetahui indeks karies gigi anak. Hasil uji analisis menggunakan chi square.Hasil: Uji analisis didapatkan hasil berupa nilai p = 0,041 untuk hubungan volume saliva terhadap kejadian karies anak dan p= 0,028 untuk hubungan pH saliva terhadap kejadian karies anak.Kesimpulan: terdapat hubungan antara volume dan derajat keaasaman (pH) saliva terhadap kejadian karies anak usia 7-9 tahun di Sekolah Dasar Negeri 5 Sumerta Denpasar, Bali.